The effect of the gonial angle, ramus length, age and gender on the temporomandibular opening index - Moipolai, Pusetso (My University, 2014)
Disorders of the temporomandibular joint (TMD) are the most common chronic pain conditions in the dental population. The cardinal signs and symptoms of these disorders are pain in orofacial muscles and / or joints; joint sounds; and limitation o f mandibular movement. Limitation of mandibular movement is usually assessed by measuring linear mouth opening. However, this has a number o f limitations. It is dependent on variables such as age, gender and ramus length. A new measure o f movement was therefore developed, the temporomandibular opening index, which was found, in a limited study to be independent of age and gender. In this study, several variables - age., gender, gonial angle and ramus length - were studied to determine their effect, on the temporomandibular opening index. This temporomandibular opening index was determined as a ratio between active (voluntary) and passive mouth opening (Miller et al., 1999). Forty-two subjects who did not exhibit signs and symptoms o f TMD were recruited to the study. Ramus length, gonial angle, gender, and age were tested for association with the temporomandibular opening index. Linear regression analysis showed that there was no evidence o f a relationship between the TOI and any o f the variables tested. The analysis showed that the temporomandibular opening index was not dependent on gender (p>0.644); gonial angle (p>0.327); ramus length (p>0.248) and age (p>0.690). This suggests that, as the temporomandibular opening index is also independent o f both age and gender, it is a better indicator o f limitation of oral opening than linear mouth opening measurements. In addition, it can also be used to categorise TMD patients. It is a cost effective, simple aid in the diagnosis o f these disorders.
Keywords: Temporomandibular Joint Disorders